Therapeutic drug monitoring of gabapentin: the applicability in patients with neuropathic pain - Yamamoto, Priscila Akemi [UNESP]; Benzi, Jhohann Richard de Lima; Dach, Fabíola; de Moraes, Natália Valadares [UNESP] (FapUNIFESP (SciELO), 2022)
Gabapentin is an antiepileptic drug prescribed for several neuropathic pain conditions. This study aimed to evaluate gabapentin (GAB) trough plasma concentration range and the applicability of therapeutic drug monitoring in patients with neuropathic pain. Fifty-three patients with neuropathic pain, aged 20 to 75, received gabapentin as treatment for at least 7 days. Gabapentin plasma concentration was sampled before GAB administration and quantified by liquid chromatography with a UV detector. GAB trough plasma concentration ranged between 0.40 and 11.94 µg/mL in patients with chronic neuropathic pain. No differences were observed in terms of GAB plasma concentrations between responsive and non-responsive patients. Our data suggest that the reference ranges suggested in the literature for patients with epilepsy should not be used for patients with neuropathic pain. Therapeutic drug monitoring of GAB was shown to be an important tool to assess treatment adherence.
Keywords: Gabapentin; Neuropathic pain; Therapeutic drug monitoring